Analisis Pola Komunikasi Keluarga dalam Pengambilan Keputusan pada Pasangan Menikah Muda di Lekok Pasuruan - Najib, Muhammad Ainun (Icon: Islamic Communication and Contemporary Media Studies, 2023)
The problem in young marriage is not about being too young or having low education but rather the readiness of the person to get married, both mentally, physically and financially. Communication patterns in the family are important in decision making for couples who are going to get married. The purpose of this study was to determine the factors that influence young married couples in Jatirejo Village, Lekok District, Pasuruan Regency, and to determine the pattern of family communication in decision making for young married couples. This study uses a descriptive qualitative research method with a field research type. Determination of subjects using purposive sampling. Data collection techniques use observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. While the validity of the data applies source and technique triangulation techniques. The results of the study showed that the factors that influence young married couples in Jatirejo Village, Lekok District, Pasuruan Regency, are education, environment, customs, economy, and pregnancy out of wedlock. While for the pattern of family communication in decision making for young married couples, it is known to use an unbalanced split pattern.